Reconciliation villages in post-genocide Rwanda, beyond rhetoric to practical reconciliation and psychosocial reintegration - Felix Bigabo; Emmanuel Biracyaza; Clementine Kanazayire; Jeannette Kangabe; Darius Gishoma (Discover Social Science and Health)
Abstract Background The 1994 genocide against the Tutsis in Rwanda resulted in the tragic loss of over one million lives and severely damaged social fabric of the country. The long-term effects of this massacre are most apparent in the persistent psychosocial challenges affecting multiple generations. In response, Prison Fellowship Rwanda introduced the Action-Based Reconciliation Model (ABRM), which has shown a noticeable impact on reconciliation and psychosocial healing. However, this model has not been extensively investigated. Thus, this study explored the prominence of ABRM in fostering psychosocial recovery and practical reconciliation in Rwanda. Methods This research employed qualitative research design to explore the impact of ABRM on psychosocial healing and reconciliation among genocide survivors and perpetrators living in reconciliation villages and neighbouring communities. Data collection involved 12 focus group discussions, with six groups from reconciliation villages and six from surrounding communities. Discussions were structured to capture experiences, perceptions and interactions of participants. All discussions were transcribed verbatim and analyzed using thematic analyses. Results Genocide survivors reported experiencing depression, hopelessness, resentment, and trauma before moving to reconciliation villages, while the families of perpetrators dealt with fear, shame, guilt, and self-stigma. Both groups indicated that living in reconciliation villages fostered a sense of re-humanization. This shared journey toward healing involved forgiveness and repentance, leading to practical reconciliation, trust, and improved social cohesion. The environment within the villages facilitated collaboration, the restoration of friendships, and positive coexistence. However, communities outside the reconciliation villages reported ongoing wounds among survivors and former prisoners, which impeded social cohesion and trust, particularly in comparison to those within reconciliation villages. Conclusion While ABRM has noticeably facilitated reconciliation and psychosocial healing, obstacles remain extant such as reluctance of ex-prisoners to openly share their experiences, and persistent psychological distresses linked to limited livelihood resources. Policymakers should continue to support these initiatives and promote international collaboration with organizations and peace-building agencies to exchange knowledge and resources, ensuring the successful implementation of reconciliation actions.